An open‐label phase I trial of a live attenuated H2N2 influenza virus vaccine in healthy adults. Issue 1 (14th March 2012) - Talaat, Kawsar R.; Karron, Ruth A.; Liang, Philana H.; McMahon, Bridget A.; Luke, Catherine J.; Thumar, Bhagvanji; Chen, Grace L.; Min, Ji‐Young; Lamirande, Elaine W.; Jin, Hong; Coelingh, Kathy L.; Kemble, George W.; et al.
Abstract : Please cite this paper as: Talaat et al. (2012) An open‐label phase I trial of a live attenuated H2N2 influenza virus vaccine in healthy adults. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2012.00350.x. Background  Live attenuated influenza vaccines (LAIV) against a variety of strains of pandemic potential are being developed and tested. We describe the results of an open‐label phase I trial of a live attenuated H2N2 virus vaccine. Objectives  To evaluate the safety, infectivity, and immunogenicity of a live attenuated H2N2 influenza virus vaccine. Participants/methods  The A/Ann Arbor/6/60 (H2N2) virus used in this study is the attenuated, cold‐adapted, temperature‐sensitive strain that provides the genetic backbone of seasonal LAIV (MedImmune). We evaluated the safety, infectivity, and immunogenicity of two doses of 10 7 TCID50 of this vaccine administered by nasal spray 4 weeks apart to normal healthy seronegative adults. Results  Twenty‐one participants received a first dose of the vaccine; 18 participants received a second dose. No serious adverse events occurred during the trial. The most common adverse events after vaccination were headache and musculoskeletal pain. The vaccine was restricted in replication: 24% and 17% had virus detectable by culture or rRT‐PCR after the first and second dose, respectively. Antibody responses to the vaccine were also restricted: 24% of participants developed an antibody response as measured by either hemagglutination‐inhibition assay (10%), or ELISA for H2 HA‐specific serum IgG (24%) or IgA (16%) after either one or two doses. None of the participants had a neutralizing antibody response. Vaccine‐specific IgG‐secreting cells as measured by enzyme‐linked immunospot increased from a mean of 0·5 to 2·0/10 6 peripheral blood mononuclear cells (PBMCs); vaccine‐specific IgA‐secreting cells increased from 0·1 to 0·5/10 6 PBMCs. Conclusions  The live attenuated H2N2 1960 AA ca vaccine demonstrated a safety profile consistent with seasonal trivalent LAIV but was restricted in replication and minimally immunogenic in healthy seronegative adults.